Analisis Indeks Kemandirian Desa Kabupaten Banjar - Nawal Nawal; Ahmad Yunani (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
In this research, the problem is how the index of village independence in Banjar Regency is and how is the economic competitiveness of villages in Banjar Regency. In general, this study aims to determine the index of village independence and the economic competitiveness of villages in Banjar Regency. This study used a quantitative descriptive approach, while the data collection techniques were conducted by interview and documentation, and the data analysis technique used was a descriptive, interpretive.From the study results, it was found that most villages in Banjar Regency were classified as developing. Based on IKS data, which reached the Village Independence Index, which was 7.22%; based on IKE data, it got the Village Independence Index, which was 0.72%; and based on IKL data, which reached the Village Independence Index, which was 6.50%. The economic competitiveness of villages in Banjar Regency is between towns with a developing classification, which is 214 villages, and an advanced type, which is 11 villages; this competitiveness can be seen from the adequate facilities in the town.